THE IMPACT OF GOVERNMENT SOCIAL ASSISTANCE ON COMMUNITY SURVIVAL DURING THE 2021 COVID-19 PANDEMIC: CASE STUDY OF BONE REGENCY, SOUTH SULAWESI - Ahmad, Ahmad; Syarifah, Syarifah (Journal of Social Politics and Governance (JSPG), 2024)
This study aims to examine the effect of social assistance on community survival during the Covid-19 pandemic in Bone Regency. The government's efforts in distributing social aid through money, goods, or services transfers by the central/regional government aim to improve social welfare, protect the community from social risks, and support the community's economic capacity. This study uses a quantitative method with data obtained from 51 respondents through a Google Form questionnaire, and data analysis is carried out using SmartPLS software. The theory used is the EUCS (End User Computing Satisfaction) model to test the effect of social assistance through the variables of Direct Cash Assistance, Basic Food Package Assistance, Family Hope Program, and Cash Social Assistance on community survival. The results of the study showed that the variables Direct Cash Assistance, Family Hope Program, and Cash Social Assistance had a significant positive effect on the survival of the Bone Regency community. Meanwhile, the Basic Food Package Assistance variable did not show a significant impact. Based on the R-Square value of 0.851, it can be concluded that the contribution of these variables to community survival reached 85.1%.